Team-Based Learning methodology applied to the construction of a child delivery plan model - Renata Marien Knupp Medeiros; Áurea Christina de Paula Corrêa; Mara Regina Rosa Ribeiro; Luanna Arruda e Silva Dalprá; Angélica Pereira Borges (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to report an experience using the Team-Based Learning methodology for the development of a standard model for Birth Plans by health professionals. Methods: experience report on the use of Team-Based Learning to develop care technology, with the participation of 120 professionals from two municipalities located in the Midwest Region. Results: the use of Team-Based Learning in this experience enabled the construction of a Child Delivery Plan model based on the theoretical approach to the theme, a critical reflection exercise, an in-depth discussion, decision-making, after what a consensus was reached. The methodology enabled the (co) construction of knowledge in small groups, teamwork, accountability, and satisfaction among the participants. Final Considerations: the use of the TeamBased Learning methodology proved to be effective as a discussion strategy, building consensus and syntheses for the elaboration of a care technology aimed at the pregnancy-parturition period.